RETROSPECTIVE ANALYSIS OF BRUCELLOSIS AMONG REGIONS AMONG BLOOD DONORS (E Global Congress, 2025)
Continuous information and up-to-date information on infectious diseases that can be transmitted through blood transfusions are transmitted through blood transfusions it is necessary to report adverse events that are a component of disease control. [1,3]. Although the risk of transmission of blood transfusion infections is lower than ever today, in the delivery of safe blood products, it remains under contamination with known and not yet identified pathogens (or infections). Only improving and implementing donor selection, sensitive screening tests, and effective inactivation practices can ensure that transfusion-transmitted infections eliminate or reduce the risk of transmission in the absence.[1]. Since the 1950s, it has been known about the risk of contracting brucellosis with blood transfusions [2,3]. Brucellosis is a zoonotic infectious and allergic disease, prone to chronic conditions, accompanied by systemic major damage to the musculoskeletal system, cardiovascular, nervous and genital organs. Brucellosis is widespread in more than 170 countries and regions of the world. [1,2]